Uncertainty in the Norwegian national transportation model - Grue, Berit (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
Monte Carlo simulations on the national transport model to examine the effects from variances in parameter estimates. The model system is run with different sets of randomly selected values for important parameters related to income and transport quality.